A Long‐Lasting Skin Protectant Based on CG‐101, a Deep Eutectic Solvent Comprising Choline and Geranic Acid. Issue 11 (4th September 2022) - Shevachman, Marina; Mandal, Abhirup; Gelston, Kevin; Mitragotri, Samir; Joshi, Nitin
Abstract: The COVID‐19 public health crisis has spotlighted the need to improve global hygiene and sanitization. In addition to causing staggering rates of transmission and fatality, COVID‐19 has severely impacted the quality of life and mental health of global citizens. The World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) encourage hand hygiene as the first defense against the spread of infection, yet frequent handwashing is often impractical. Widely used ethanol‐based hand sanitizers provide immediate protection against pathogens on the skin, albeit short‐lived, due to their rapid evaporation. Herein, a novel, long‐lasting skin protectant formulated with biocompatible ionic liquid/deep eutectic solvents prepared using generally recognized as safe materials – choline and geranic acid (CG‐101, 5% w/w) – is described. In vitro studies demonstrated that CG‐101 inactivates bacteria and the human coronavirus, hCoV229E, for 4 h after application. Two human clinical studies demonstrate that CG‐101 does not cause skin irritation or sensitization, and a single application of CG‐101 gel imparts skin protection against microbes for significantly longer than conventional 70% ethanol‐based hand sanitizers. These data are the first to indicate that CG‐101 may be a better alternative to alcohol‐based hand sanitizers for long‐term skin protection against infectious diseases. Abstract : The pandemic has highlighted the need to improve global hygiene. A novel skin protectant containing biocompatible the ionic liquid, choline geranate (CG‐101), provides sustained protection from harmful pathogens including human coronavirus for 4 h. Data from human trials demonstrate that CG‐101 does not cause skin irritation, and a single application of CG‐101 gel imparts protection significantly longer than ethanol‐based sanitizers.